Demographic and behavioral characteristics of non-sex worker females attending sexually transmitted disease clinics in Japan: a nationwide case-control study - Kato Hideko; Sato Tatsuya; Ono-Kihara Masako; Suguimoto-Watanabe Sonia P; Zamani Saman; Kihara Masahiro (BMC, 2010)
Abstract Background Although number of sexually transmitted infections (STIs) reported in STI surveillance increased rapidly for women in Japan during the 1990s, the sexual behavior of women potentially at risk of STI infection remains unknown. Methods In order to determine the demographic and behavioral characteristics of non-sex worker (SW) females attending STI clinics, female attendees (n = 145), excluding SW, from nine clinics across Japan and female controls from the general population (n = 956), both aged 18-50 years, were compared using two data sets of nationwide sexual behavior surveys conducted in 1999. Results Although the occupation-type and education level were unrelated to STI clinic attendance in multivariate analysis, non-SW females attending STI clinics were younger (adjusted odds ratios [AOR] = 0.94, 95%CI: 0.89, 0.99), and more likely to be unmarried (AOR = 4.11, 95% CI: 1.73, 9.77) than the controls from the general population. In the previous year, STI clinic attendees were more likely to have had multiple partnerships (AOR = 3.09, 95% CI: 1.42, 6.71) and unprotected vaginal sex with regular partners (AOR = 3.59, 95% CI: 1.49, 8.64), and tended to have had their first sexual intercourse at a younger age (AOR = 1.77, 95%CI: 0.89, 3.54) and more unprotected vaginal and/or oral sex with casual partners (AOR = 2.08, 95%CI: 0.75, 5.71). Identical sexual behavior patterns were observed between the female attendees with a current diagnosis of STI (n = 72) and those before diagnosis (n = 73) and between those with a past history of STI (n = 66) and those without (n = 79). Conclusion These results indicate that not only multiple partnerships or unprotected sex with casual partners, but also unprotected vaginal sex within a regular partnership is prevalent among non-SW female STI clinic attendees. The identical sexual behavior patterns observed between female attendees with a current STI diagnosis and those without, and between those attendees with a past history of STI diagnosis and those without, indicate that the result are unlikely confounded with the cases of non-STI infection. This sexual behavior pattern may be predictive of STI infection among young Japanese women and could have contributed to the STI epidemic in women in Japan during the 1990s.